Pengaruh Pertumbuhan Ekonomi Tingkat Pendidikan dan Pengangguran Terhadap Kemiskinan di Indonesia Periode 2015-2022 - Pusfita, Ayu Tika; Musthofa, Muhammad Wakhid (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to understand the relationship between economic growth, educational levels and distribution regarding poverty levels in Indonesia for 2015-2022. The method in this research is qualitative with secondary data obtained from the Baldaln Statistical Center. The digital analysis technique used is the digital panel regression method using E-Views 10. The results of this research show that although the estimated coefficient of economic growth is not significant in probability value, it has a positive but not significant influence on poverty levels. The estimated coefficient for educational level is not significant with a probability value of 0, has a negative and significant influence on poverty levels, the estimated coefficient of poverty has a significant probability value, has a positive and significant influence on poverty levels.